2017
DOI: 10.1101/112458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective purifying selection in ancient asexual oribatid mites

Abstract: Sex is beneficial in the long term because it can prevent mutational meltdown through increased effectiveness of selection. This idea is supported by empirical evidence of deleterious mutation accumulation in species with a recent transition to asexuality. Here, we study the effectiveness of purifying selection in oribatid mites which have lost sex millions of years ago and diversified into different families and species while reproducing asexually. We compare the accumulation of deleterious nonsynonymous and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…However, in only eight studies were the tests conducted genome-wide, while tests in the remaining studies were based on only one or a few genes. Note that four [52,[54][55][56] of the genome-wide studies were based on transcriptomes and are therefore not included in our systematic reanalysis. Among the genome-wide tests, results are much more mixed than among the studies on few genes, raising the question whether the latter are representative of the genome as a whole.…”
Section: Mutation Accumulation and Positive Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in only eight studies were the tests conducted genome-wide, while tests in the remaining studies were based on only one or a few genes. Note that four [52,[54][55][56] of the genome-wide studies were based on transcriptomes and are therefore not included in our systematic reanalysis. Among the genome-wide tests, results are much more mixed than among the studies on few genes, raising the question whether the latter are representative of the genome as a whole.…”
Section: Mutation Accumulation and Positive Selectionmentioning
confidence: 99%
“…Specifically, only two of the eight genomewide studies support deleterious mutation accumulation in asexuals (stick insects and evening-primroses) [52,54]. Moreover, two studies found more deleterious mutation accumulation in sexual than asexual taxa (parasitoid wasps and oribatid mites) [21,55], while the four remaining ones found no differences between sexual and asexual taxa [17,23,27,56]. In the case of the water flea D. pulex, the study specifically reported that earlier inferences of deleterious mutation accumulation under asexuality were incorrect, as the deleterious mutations detected in asexual strains were inherited from the sexual ancestor and not accumulated after the transition to asexuality [27].…”
Section: Mutation Accumulation and Positive Selectionmentioning
confidence: 99%
“…Most cases (14 out of 19 cases; Table 1) that, as expected, asexuals had a higher load of deleterious mutations than sexuals. The fourth 305 study (Brandt et al 2017) found that sexual taxa experienced more mutation accumulation than 306 asexual counterparts. This latter study focused on asexual lineages that are extremely old (tens of 307 million years since derivation from sexual ancestors), suggesting that the absence of deleterious 308 mutation accumulation may have contributed to the long-term persistence of these lineages in the 309 absence of sex.…”
Section: Mutation Accumulation 296mentioning
confidence: 99%
“…Because of this among-gene variation, the inferences generated by the 15 cases that only 388 included a handful of genes must be viewed with caution. Indeed, one of the four cases that did 389 investigate mutation accumulation at the whole-genome scale in the wild found that, contrary to 390 predictions, sexual taxa experienced more mutation accumulation (Brandt et al 2017). Finally, 391 although there appears to be some general support for deleterious mutation accumulation in 392 asexual lineages, it is important to note that this mechanism is unlikely to explain the 393 maintenance of sex.…”
mentioning
confidence: 93%
“…Theory predicts that a lack of recombination can lead to increased heterozygosity in asexual compared to sexual genotypes (Birky 1996;Mark Welch & Meselson 2000;Judson & Normark 1996). Several studies have tested this prediction, usually by comparing related species with different reproductive modes (Bast et al 2018;Brandt et al 2017Brandt et al , 2021Henry et al 2012;Hollister et al 2015;Lovell et al 2017;Schwander et al 2011), which can make it difficult to discern genetic difference due to reproductive mode from those owing to other species-specific differences in life-history and population ecology. Other studies involve asexual lineages that arose through hybridization and/or polyploidy (Ament-Velásquez et al2016;Flot et al 2013;Johnson & Howard 2007;Koči et al 2020;Neiman et al 2010;Pellino et al 2013;Sharbrough et al 2018), which also obfuscates the impacts of asexuality.…”
Section: Introductionmentioning
confidence: 99%